Pengaruh agunan dan profitabilitas terhadap tingkat hutang perusahaan dimoderasi oleh umur perusahaan - Nikolas, Samuel; Purwaningsih, Eny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The capital structure is reflected in the ratio of total debt (short-term plus long-term) to total assets. Leverage is a comparison between a company's long-term funding between long-term debt and total assets. The level of debt is important for the company's business continuity, when the company experiences a funding deficit after using its own capital, the company will use debt as a source of funds from outside the company. There are factors that can affect debt levels such as COL, AGE and NPM. This study was conducted to determine the effect of COL and NPM moderated by the age of the company on the level of company debt. The gap theory in this study is that there are differences in results in profitability variables so that researchers are interested in re-examining to see the results. The population of this study used companies in the various industries sector for the 2016-2020 period amounted to 44 companies and the sample obtained was 11 companies using purposive sampling techniques. The analysis in this study used descriptive statistics, then the pituitary test used moderation regression analysis. The results of this study indicate that partially collateral has a negative effect on the level of debt, profitability has no effect on the level of debt, the age of the company strengthens the effect of collateral on the level of debt and the age of the company does not moderating the effect of profitability on debt levels.